An Account of the Antiquities of the Indians : A New Edition, with an Introductory Study, Notes, and Appendices by José Juan Arrom - Pane, Ramón, -1571 (Latin America in translation/en traducción/em tradução., 2019)
Accompanying Columbus on his second voyage to the New World in 1494 was a young Spanish friar named Ramón Pane. The friar's assignment was to live among the "Indians" whom Columbus had "discovered" on the island of Hispaniola (today the island shared by Haiti and the Dominican Republic), to learn their language, and to write a record of their lives and beliefs. While the culture of these indigenous people--who came to be known as the Taíno--is now extinct, the written record completed by Pane around 1498 has survived. This volume makes Pane's landmark Account--the first book written in a European language on American soil--available in an annotated English edition. Edited by the noted Hispanist Jose Juan Arrom, Pane's report is the only surviving direct source of information about the myths, ceremonies, and lives of the New World inhabitants whom Columbus first encountered. The friar's text contains many linguistic and cultural observations, including descriptions of the Taíno people's healing rituals and their beliefs about their souls after death. Pane provides the first known description of the use of the hallucinogen cohoba, and he recounts the use of idols in ritual ceremonies. The names, functions, and attributes of native gods; the mythological origin of the aboriginal people's attitudes toward sex and gender; and their rich stories of creation are described as well.